2005
DOI: 10.1080/0026897041233336264
|View full text |Cite
|
Sign up to set email alerts
|

Ionic mobility and ionic association of singly charged ions in glycerol

Abstract: Experimental molar conductivity data for KCl, NaCl and LiCl in glycerol at 298.15 K were analysed by least-square fitting in the concentration range 0.5-100 mol m À3 in order to compute the values of the molar conductivity at infinite dilution à 0 and the Onsager constant S. Using previously measured transference numbers and assuming the Kohlrausch infinite dilution law, the limiting ionic mobilities were deduced. The results obtained show that the transport mechanisms in this solvent and other similar hydroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
1
3
0
1
Order By: Relevance
“…Notably, neither the temperature nor the precursor Ca/P ratio nor the total concentration had an effect on the final Ca/P ratio in the crystals, indicating that the Ca deficiency is not the result of limited Ca ion supply or diffusion during crystallization. This conclusion is in line with the fact that the Ca/P ratio was identical in platelets produced in glycerol, a solvent exhibiting a 30-fold lower ionic mobility compared with ethylene glycol due to its higher viscosity (Kameche et al, 2005). Also, since the final stoichiometry was independent of the reaction time (varying from 1 min to 24 h), the Ca deficiency cannot be a result of Ca diffusing out of the crystals after their formation.…”
Section: àsupporting
confidence: 72%
“…Notably, neither the temperature nor the precursor Ca/P ratio nor the total concentration had an effect on the final Ca/P ratio in the crystals, indicating that the Ca deficiency is not the result of limited Ca ion supply or diffusion during crystallization. This conclusion is in line with the fact that the Ca/P ratio was identical in platelets produced in glycerol, a solvent exhibiting a 30-fold lower ionic mobility compared with ethylene glycol due to its higher viscosity (Kameche et al, 2005). Also, since the final stoichiometry was independent of the reaction time (varying from 1 min to 24 h), the Ca deficiency cannot be a result of Ca diffusing out of the crystals after their formation.…”
Section: àsupporting
confidence: 72%
“…One of reasons for high conductivity of proposed hydrogels is optimal content of solvent embedded within the polymer matrix that ensures good mechanical strength without sacrificing the ionic mobility. With this, electrolytes proposed in this study surpass the conductivity threshold reported for polymer electrolytes used in leakage-free (flexible, stretchable) energy sources (up to 10 À 4 S cm À 1 [28] ). Notably, the effect of glycerol content on ionic conductance at room temperature is significant (Figure 4a).…”
Section: Resultsmentioning
confidence: 63%
“…Table 6 lists the mixed-solvents electrolyte solutions for which association and stability data were available. The majority of the data are for symmetrical univalent electrolytes, particularly alkali halides, in pure nonaqueous (Hoshina et al, 2004;Kameche et al, 2005;Wurm et al, 2005) and mixed aqueous-organic solvents. In comparison, little information was available for symmetric polyvalent (Molinou and Tsierkezos, 2001;Molinou, 2000, 2006) and unsymmetric electrolytes (K 2 SO 4 , Na 2 SO 4 , Cd(NO 3 ) 2 , CdCl 2 , CaCl 2 , Ca(NO 3 ) 2 , CoCl 2 , and Zn(NO 3 ) 2 ) in nonaqueous (e.g., Gibson et al, 2006;Pura, 2007) or mixed solvents (Fujii et al, 2006;Qiao et al, 2008).…”
Section: Downloaded By [Northeastern University] At 07:36 27 Novembermentioning
confidence: 97%